Pengaruh Financial Knowledge dan Financial Attitude Terhadap Financial Management Behavior - Afriyanto, Dika; Fathihani, Fathihani (Journal of Fundamental Management (JFM), 2023)
This research aims to determine how final knowledge and final attitude can influence financial management behavior. It is hoped that the results of this research will contribute to being wiser in managing finances and prioritizing needs over desires. The population used was Dian Nusantara University students. The sample used was 140 respondents spread across the Jakarta area. Data collection was carried out using a questionnaire method where respondents answered questions arranged in choice form and the question scale used a Likert scale (1-5). The method used in this research is quantitative analysis with the SEM analysis tool and the SmartPLS 3.3 tool. The results show that final knowledge and final attitude have a positive effect on financial management behavior.